2006
DOI: 10.17221/3363-pse
|View full text |Cite
|
Sign up to set email alerts
|

Soybean (Glycine max) seed growth characteristics in response to light enrichment and shading

Abstract: Seeds are the primary sinks for photosynthates during reproductive growth. Variation in light intercepted during and after seed initiation has been found a major environmental determinant of soybean [Glycine max (L.) Merrill] seed size. We investigated the influence of light enrichment and shading on seed growth rate, effective filling, cotyledon cell number, cell volume and endogenous ABA concentrations of cotyledons/testas during seed filling of soybean. Evans, an indeterminate Group 0 soybean, was subjected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
9
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 33 publications
5
9
0
1
Order By: Relevance
“…The increase in PGR from planting to physiological maturity indicated that PGR for all genotypes followed the normal growth rate curve, which usually increases as plant growth duration increase. Similar results have been reported on soybean, barley and maize [45,46,47,48]. Increased PGR from planting to budding at 15/20˚C temperature regime and decrease from budding to flowering and flowering to physiological maturity suggest that increasing the mean night/day temperature from 12.5˚C to 17.5˚C increased PGR during the vegetative growth stage (planting to budding) by increasing the rate of leaf appearance and expansion, but as growth progress the increase in temperature decreased PGR by increasing the rate of leaf senescence and respiratory break down of photosynthates [49,50,51].…”
Section: Effect Of Temperature On Plant Growth Rate (Pgr) Relative Gsupporting
confidence: 89%
“…The increase in PGR from planting to physiological maturity indicated that PGR for all genotypes followed the normal growth rate curve, which usually increases as plant growth duration increase. Similar results have been reported on soybean, barley and maize [45,46,47,48]. Increased PGR from planting to budding at 15/20˚C temperature regime and decrease from budding to flowering and flowering to physiological maturity suggest that increasing the mean night/day temperature from 12.5˚C to 17.5˚C increased PGR during the vegetative growth stage (planting to budding) by increasing the rate of leaf appearance and expansion, but as growth progress the increase in temperature decreased PGR by increasing the rate of leaf senescence and respiratory break down of photosynthates [49,50,51].…”
Section: Effect Of Temperature On Plant Growth Rate (Pgr) Relative Gsupporting
confidence: 89%
“…Decrease of seed size in D27 of H339 in 2007 and D27 of H339 in 2008 might be caused by the greater increase of seed number per plant than increase of available amount of photosynthate synthesized per plant under the light enrichment condition. Liu et al (2006a) noticed that shading (52% light reduction) lowered seed size while Egli et al (1985) reported that shading (60% light reduction) during the linear phase of seed development lowered seed growth rate but did not affect final seed size because of a longer duration of seed growth. In our study, shading (25% light reduction) increased seed size by 7 to 11%, which might be a compensation mechanism to yield loss.…”
Section: Resultsmentioning
confidence: 99%
“…While studying the problem of low luminosity, Liu et al (2010) and Liu et al (2006) concluded that the occurrence of long periods of greater cloud cover can cause photosynthetic deficiency and, as a consequence, a reduction in yield. According to Santos et al (2003), in common beans, soybeans and weed plants, the yield is generally limited by photosynthetic capacity from the start of pod formation and as a result, a reduction in the rate of photosynthesis causes variations in the grain yield or biomass production.…”
Section: Acta Scientiarum Agronomymentioning
confidence: 99%